Ø´Ø®ØµÙŠØ§Øª Ø§Ù„Ø£Ø´Ø®Ø§Øµ Ø¹Ù†Ø¯ Ø³ÙŠØºÙ…ÙˆÙ†Ø¯ ÙØ±ÙˆÙŠØ¯ ÙÙŠ Ø±ÙˆØ§ÙŠØ© "Ø§Ù„Ø±Ø¬Ù„ Ø§Ù„Ø°ÙŠ Ø¢Ù…Ù†" Ù„Ù†Ø¬ÙŠØ¨ Ø§Ù„ÙƒÙŠÙ„Ø§Ù†ÙŠ (Ø¯Ø±Ø§Ø³Ø© Ø³ÙŠÙƒÙˆÙ„ÙˆØ¬ÙŠØ© Ø£Ø¯Ø¨ÙŠØ©) - Pretty Putri Isdamanto (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2017)
Novel "Arrajul al Lazi Amana" is a novel by Najib Kaelani. In this novel Kaelani Najib Describes about the discovery of a new life. Old-paced modern environment did not provide Iryan happiness. West telahdigapai progress it gave birth to her alienation. So he chose to go to the east to find a new path. Arriving in the East, he gets the desired. An old belief, Christian. Abandoned to embrace a new faith, Islam. After embracing this new confidence he gained a light heart, which changed his life. He left his fame and the glitzy world of music. He chose bersunyi ourselves in God's way. Sings music he changed into a chant to God, until he gained true happiness. The purpose of this study was to describe the character of the characters in the novel "Arrajul al Lazi Amana" .And focus the problems presented in this discussion are: 1). How many characters in the novel "Arrajul al Lazi Amana" by Najib Kaelani ?, 2) How does the character figures according to Sigmund Freud's theory of the novel "Arrajul al Lazi Amana" Najib Kaelani work ?. The method used in this research is descriptive qualitative method. The approach used in this study is the approach of psychology literature. Data generated in the form of words in the form of quotations from the text of the novel. In connection with that, in this study used the psychoanalytic theory of Sigmund Freud that focuses on understanding the dynamics of the character and personality of a person or particular on the characters in the novel "Arrajul al Lazi Amana". Because this story about the discovery of new life in the novel "Arrajul al Lazi Amana" is more inviting elements of the psyche.